Effect of lung transplantation on diaphragmatic function in patients with chronic obstructive pulmonary disease. Issue 5 (May 1994) - Wanke, T; Merkle, M; Formanek, D; Zifko, U; Wieselthaler, G; Zwick, H; Klepetko, W; Burghuber, O C
Abstract : BACKGROUND–To date there are no data on the effects of lung transplantation on diaphragmatic function in patients with end stage chronic obstructive pulmonary disease (COPD). It is not known whether the relation between the transdiaphragmatic pressure (PDI) and lung volume is altered in recipients after transplantation as a result of changes in diaphragmatic structure caused by chronic hyperinflation. The effect of lung transplantation on diaphragmatic strength was determined in patients with COPD and the relation between postoperative PDI and lung volume analysed. METHODS–Diaphragmatic strength was assessed in eight double lung transplant recipients, six single lung transplant recipients, and in 14 patients with COPD whose lung function was similar to those of the transplant recipients preoperatively. PDI obtained during unilateral and bilateral phrenic nerve stimulation at 1 Hz (twitch PDI) at functional residual capacity (FRC) and during maximal sniff manoeuvres (sniff PDI) at various levels of inspiratory vital capacity (VCin) served as parameters for diaphragmatic strength. Sniff PDI assessed at the various VCin levels were used to analyse the PDI/lung volume relation. RESULTS–Lung transplantation caused a reduction in lung volume, especially in the double lung transplant recipients. As a consequence sniff PDI was higher in the double lung transplant recipients than in the patients with COPD at all levels of VCin analysed. However, sniff PDI values analysed at comparable intrathoracic gas volumes were not reduced in the patients with COPD when compared with those who underwent lung transplantation. Bilateral twitch PDI values were similar in the patients with COPD and in the lung transplant recipients. In the single lung transplant recipients unilateral twitch PDI values were similar on the transplanted and the non-transplanted side. The relation between PDI and lung volume was similar in the patients with COPD and in the lung transplant recipients. CONCLUSIONS–In patients with COPD lung transplantation leads to an increase the maximal sniff induced PDI values by placing the diaphragm in a more favourable position for pressure generation. Since patients with COPD and postoperative lung transplant recipients showed similar PDI/lung volume relations, this suggests that chronic pulmonary hyperinflation does not cause major functional alterations of the diaphragm.